Pentingnya Proses Evaluasi Dalam Pembelajaran Di Sekolah Dasar - Ina Magdalena; Gilang Ramadhan; Hasanah Dwi Wahyuni; Nabilah Dwi Safitri (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This article discusses the importance of the evaluation process in elementary school learning. Evaluation plays a crucial role in determining the effectiveness of learning and the achievement of educational goals. Evaluation helps teachers obtain valid data on students' abilities, identify their learning difficulties, and understand their position among their peers. Through evaluation, teachers can make professional decisions in developing their teaching methods. The article emphasizes the significance of understanding and skills in conducting effective evaluation. Evaluation should not only be carried out at the end of a lesson but throughout the entire learning process. By conducting accurate and comprehensive evaluations, educators can gather precise information about students' abilities, enabling them to make informed decisions in their teaching practices. Improving understanding and implementing effective evaluation processes contributes to enhancing the quality of elementary school education. Effective evaluation not only benefits teachers in decision-making but also helps improve self-quality and classroom management.